PENERAPAN TEKNIK TERATAI (TERJUN AMATI RANGKAI) DALAM PEMBELAJARAN MENULIS CERPEN - Meilani, Frida Sri (2015)
Penelitian ini dilatarbelakangi oleh kurangnya minat siswa dalam pembelajaran menulis teks sastra di sekolah, khususnya teks cerita pendek yang disebabkan sulitnya siswa untuk menemukan ide-ide dalam awal penulisan cerita oleh sebab itu siswa sering merasa bosan dalam pembelajaran menulis cerpen. Berdasarkan hal tersebut, peneliti menguji penerapan teknik teratai (terjun amati rangkai) dalam pembelajaran menulis cerpen di kelas XI. Tujuan dari penelitian ini, yaitu untuk mengetahui kemampuan menulis teks cerita pendek siswa pada kelas eksperimen sebelum dan sesudah menggunakan teknik teratai (terjun amati rangkai) dalam pembelajaran menulis cerpen, dan untuk mengetahui kemampuan menulis teks cerita pendek siswa pada kelas kontrol. apakah terdapat perbedaan yang signifikan antara kemampuan menulis teks cerita pendek siswa di kelas eksperimen dan kelas kontrol. Teknik teratai ini bertujuan untuk mempermudah siswa dalam menemukan ide awal untuk penulisan teks cerita pendek. Penelitian ini menggunakan metode penelitian eksperimen semu atau kuasi (quasi eksperimental) dengan desain pretest-postest control group design. Desain ini melibatkan dua kelas di mana yang satu menempati kelas eksperimen berjumlah 29 siswa dan satunya merupakan kelas kontrol yang berjumlah 30 siswa yang diambil secara purposive sampling. Berdasarkan data penelitian yang telah diolah menggunakan perhitungan kuantitatif, hasil pretest dan posttest kelas eksperimen dan kelas kontrol berdistribusi normal dan homogen. Berdasarkan perhitungan uji t hipotesis, diperoleh hasil thitung (2,935) > ttabel (2,004). Hal tersebut menunjukkan bahwa teknik teratai (terjun amati rangkai) terbukti efektif dalam pembelajaran menulis cerpen pada siswa kelas XI SMA Negeri 19 Bandung. The implementation of TERATAI (Terjun amati rangkai) technique in-learning process to write a short story. A statical research to 11th grade students of SMAN 19 Bandung 2014-2015's school year. This research is conducted with a lack of interest among students to learn writing a literature in mind, especially a short story which is caused by the difficulties to find new ideas in the beginning of a story because the students tend to feel bored to learn writing a short story.nbased on the fact above, the research conducted a test of especially a short story which is caused by the difficulties to find new ideas in the beginning of a story because the students tend to feel bored to learn writing a short story.nbased on the fact above, the research conducted a test TERATAI implementation in a learning process to write a short story in 11th grade students, the purpose of this research is solely to measure the differences of students ability in experimented class before and after implementing TERATAI technique in a learning process to write a short story and also to measure the writing ability of students in controlled class before and after implementing a direct approach method, and also to identifying whether there is a significant differences between a students in experimented class and controlled class. The experiment is conducted by implementing a pseudoexperimental research method a.k.a quasi experimental with a pretest-posttest controlled group design. This design involving two classes which is divided into experimented class which is consist of 29 students, and controlled class which is consist 30 students chosen from total population with a purpose sampling method. Based on research data which has treated with a quantitative calculation the pretest and posttest of experimented and controlled class can be varied into a normal and homogeneity population. Based on the calculation and hypothesis test the result obtained is t count (2,935) t table (2,004). These result has showed us that a teratai technique has proven effective to implement in a learning process to write a short story by the 11th grader students of SMAN 19 Bandung.